THE BEHAVIOR OF SELF COMPACTING CONCRETE BEAMS REINFORCED STEEL ROUND HOLLOW PIPE IN Fc' 25 MPa CONCRETE - N. Bambang Revantoro, Arry Naufal (BANGUNAN, 2022)
Abstract: This research examines the behavior of Self Compacting Concrete beams reinforced with round hollow steel pipes on fc' 25 MPa concrete which aims to determine the effect of both types of reinforcement characteristics on flexural capacity, deflection, and crack patterns in self-compacting concrete beams reinforced with round hollow steel pipes size 1.8 x 16 x 1000 mm and plain steel reinforcement ∅10 which is used as longitudinal reinforcement. The specimen of a reinforced concrete beam with a dimension was 12 cm x 18 cm x 100 cm used 2 types of longitudinal reinforcement. BTH beams use longitudinal reinforcement from round hollow pipe steel reinforcement measuring 1.8 x 16 x 1000 mm and BTK beams use longitudinal reinforcement from steel reinforcement plain ∅10 while the stirrup reinforcement used steel reinforcement ∅6. Based on the research results, the average flexural capacity of BTK beams is 16.50 MPa and the average flexural capacity of BTH beams is 16.41 MPa. The test results of the maximum deflection of the BTK beam are 9.83 mm and the average maximum deflection of the BTH beam is 7.84 mm. The flexural capacity between the two types of beams does not have a significant difference. The maximum deflection that occurs from the BTK beam and the BTH beam does not have a significant difference. The crack pattern of all beam specimens is categorized as a flexural crack.Keywords: beam behavior, self-compacting concrete beams, round hollow pipe, steel reinforcement, concrete fc' 25 MPa